Фактори впливу на ефективність емісійної політики підприємств корпоративного типу та експертне оцінювання їх пріоритетності - Пешко, Олександр Володимирович (Київський національний університет імені Тараса Шевченка, 2024)
Проаналізувавши сукупність принципів цифрової фінансової інклюзії G 20 і адаптувавши їх до особливостей емісійної політики підприємств корпоративного типу, виокремлено фактори впливу на її ефективність в умовах цифрових перетворень і турбулентності. Залучивши експертів фондового ринку України і використавши метод кореляційного аналізу Кендала до аналізу даних опитування, визначено ступінь значущості кожного фактора щодо емісійної політики підприємств корпоративного типу і розроблено рекомендації щодо її вдосконалення.

The development of the emission policy of enterprises in recent years has been accompanied by rapid processes of digital transformation. However, the emission activity of Ukrainian corporate-type enterprises is quite restrained even on foreign stock platforms, and digital tools are not used enough both in emission activity and in the further management of the funds raised. All this makes it necessary to investigate the influence of certain factors on the effectiveness of the emission policy of corporate-type enterprises, paying special attention to those of them that are directly related to the development of information technologies. The G 20 principles of digital financial inclusion were analyzed and adapted to the specifics of the emission policy of corporate-type enterprises. Based on them, factors affecting the effectiveness of emission policy in the conditions of digital transformation and turbulence were determined. Having involved experts of the stock market of Ukraine and using the Kendall correlation analysis method to analyze the survey data, the degree of significance of each factor in relation to the emission policy of corporate-type enterprises was determined and recommendations for its improvement were developed. The obtained results, despite the recognition of the key role of the scientific and methodological basis of emission policy, the importance of developing the infrastructure of the securities market, increasing the investment attractiveness of issuers and improving measures to counter risks, testify to a certain underestimation of digital factors and an insufficient level of use of digital tools in the development and implementation of the emission policy of corporate-type enterprises. In the future, it is expedient to carry out this research, improving it by clarifying the set of factors and involving a larger number of experts, both from the stock market specialists and representatives of the management of corporate-type enterprises, who have practical experience in emission activity. This will allow, on the basis of the obtained results, to form the most formalized recommendations for increasing the efficiency of the emission policy of corporate-type enterprises in the conditions of digital transformations and turbulence.
Factors Affecting the Effectiveness of the Emission Policy of Corporate-Type Enterprises and Their Correlation Analysis
Keywords: емісійна політика; емісійна діяльність; фактори впливу; цифрова трансформація; підприємства корпоративного типу; ефективність; турбулентність; emission policy; emission activity; influencing factors; digital transformation; corporate-type enterprises; efficiency; turbulence